2017
DOI: 10.1111/ijfs.13428
|View full text |Cite
|
Sign up to set email alerts
|

Rapid detection of Listeria monocytogenes using fluorescence immunochromatographic assay combined with immunomagnetic separation technique

Abstract: Summary To ensure the safety and quality of food ingredients, especially meat and dairy products, a high‐throughput, rapid and sensitive method to detect Listeria monocytogenes (LM) is always on a high demand. In this work, a specific induction method to enrich and detect LM based on fluorescence immunochromatographic assay (FICA) combined with immunomagnetic separation (IMS) techniques has been developed. The immunomagnetic‐beads (IM) beads were obtained through functionalised magnetic microspheres and the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…Liu et al [17] showed that the combination of magnetic concentration and immunochromatography yields a 25-50-fold gain in the detection limit of aflatoxin M1 in milk compared to the variants in which magnetic or gold nanoparticles are used as conventional labels. A 40-fold gain in the detection limit was demonstrated by Lu et al [18] upon the detection of Listeria monocytogenes. In Petrakova et al [19], using the examples of zearalenone and T-2 toxin, the authors showed that magnetic nanoparticles can be used as directly detectable optical markers.…”
Section: Proper Sample For Lfiamentioning
confidence: 93%
“…Liu et al [17] showed that the combination of magnetic concentration and immunochromatography yields a 25-50-fold gain in the detection limit of aflatoxin M1 in milk compared to the variants in which magnetic or gold nanoparticles are used as conventional labels. A 40-fold gain in the detection limit was demonstrated by Lu et al [18] upon the detection of Listeria monocytogenes. In Petrakova et al [19], using the examples of zearalenone and T-2 toxin, the authors showed that magnetic nanoparticles can be used as directly detectable optical markers.…”
Section: Proper Sample For Lfiamentioning
confidence: 93%
“…In some applications, magnetic nanoparticles have been used to perform a double function simultaneously: separation and label for optical detection [25,35,78]. In other cases, gold and fluorescent nanoparticles have been employed in combination with magnetic nanoparticles in order to use optical nanoparticles for the transduction and magnetic nanoparticles for the IMS [85,88,89]. Nanocomposites combining magnetic nanoparticles with gold or fluorescent nanomaterials have also been reported to get the same double function [84,87].…”
Section: Immunomagnetic Separation In Combination With Other Transduction Systemsmentioning
confidence: 99%
“…In recent years, a growing number of studies have focused on enhancing the detection sensitivity and reducing the testing time from days to hours. The representative methods include immunology‐based methods (enzyme linked immunosorbent assay, ELISA; immunochromatographic assay, ICA), nucleic acid‐based methods (polymerase chain reaction, PCR; loop‐mediated isothermal amplification, LAMP), signal‐based methods (such as fluorochrome and quantum dots [QDs]), and so on (Bi et al., 2020; Li et al., 2017; Li et al., 2019; Park, Park, Ok, Chang, & Lim, 2020; Wei et al., 2019; Xue, Zheng, Zhang, Jin, & Lin, 2018). However, food samples are usually complex and heterogeneous systems.…”
Section: Introductionmentioning
confidence: 99%